Electroencephalograph-Based Emotion Recognition Using Brain Connectivity Feature and Domain Adaptive Residual Convolution Model - Chen, Jingxia; Min, Chongdan; Wang, Changhao; Tang, Zhezhe; Liu, Yang; Hu, Xiuwen (Frontiers in Neuroscience, 2022)
In the research of emotion recognition based on electroencephalograph (EEG), how to obtain features with more emotional information has become the key to improve the performance of emotion recognition. This paper proposes a new end-to-end emotion recognition method based on brain connectivity feature and adaptive residual convolutional network (short for BC-DA-RCNN), which could effectively extract the spatial connectivity information related to the emotional state of the human brain and introduce domain adaptation to achieve accurate emotion recognition within and across the subject’s EEG signals. The brain connectivity (BC) information is represented by the global brain network connectivity matrix. The domain adaptive residual network (DA-RCNN) is used to extract high-level emotional features between different dimensions of EEG signals, reduce the domain offset between different subjects, and strengthen the common features between different subjects. The experimental results on the large public DEAP data set show that the accuracy of the subject-dependent and subject-independent binary emotion classification in valence reaches 95.15% and 88.28%, respectively, which outperforms all the benchmark methods. The proposed method is proved to have lower complexity, better generalization ability and domain robustness that help to lay a solid foundation for development of high-performance affective brain-computer interface applications.